Captioning and subtitling for d/Deaf and hard of hearing audiences - Zárate, Soledad (UCL Press, 2021)
"Captioning and Subtitling for d/Deaf and Hard of Hearing Audiences is a comprehensive guide to the theory and practice of captioning and subtitling, with examples and exercises at the end of each chapter. Analyzing the requirements of d/Deaf and hard of hearing audiences in detail, as well as treating the linguistic and technical considerations necessary for effective captioning, this volume will familiarize the reader with the characteristics, needs, and diversity of d/Deaf and hard of hearing audiences. Based on first-hand experience in the field, the book provides a step-by-step guide to making live performances accessible to d/Deaf and hard of hearing audiences. The guide will be [a resource for] students of audiovisual translation, professional subtitlers, and captioners, as well as any organization or venue that engages with d/Deaf and hard of hearing people."--Provided by publisher.